CODE-MIXING IN SPEAKING OF TENTH GRADE STUDENTS AT SMAN 1 METRO ACCADEMIC YEAR 2019/2020 - Fitri Palupi Kusumawati; Sekar Seta Riva Putri (English Teaching and Linguistics Journal (ETLiJ), 2021)
Code-mixing is the use of two different languages in a sentence without changing the topic. The objectives of this research are to find out the types of code-mixing utilized in students speaking and to know the factors of code-mixing mostly occurred in students speaking. Due to covid-19, the researcher collects the data by using Triangulation namely Participant Observation, In-depth Interview and Documentation through Zoom and WhatsApp Application. Furthermore, analytical research is applied to analyze code-mixing in students speaking of tenth grade students at State Senior High School 1 Metro accademic year 2019/2020. Thus, the result shows that there are 23 out of 33 students use code-mixing in their speaking. It is found 45 code-mixing devided into three types including 21 Insertion which characterized by inserting one or more Indonesian vocabularies into an English sentence or utterence, 19 Alternation which characterized by the existence of clause or sentence alternation between Indonesian and English, and 5 Congruent Lexicalization which characterized by the existence of dialect from Indonesian inserted in tenth grade students English Speaking. Meanwhile, it is found that there are 4 factors of code-mixing namely interlocutor or the person whom they are talking to, culture or habit, confidence and lack of vocabulary.